The open : man and animal - Agamben, Giorgio, 1942- (Meridian (Stanford, Calif.), 2004)
In 'The Open', contemporary Italian philosopher Giorgio Agamben considers the ways in which the 'human' has been thought of as either a distinct and superior type of animal, or a kind of being that is essentially different from animal altogether.